2003
DOI: 10.1056/nejmoa035422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Intensity Warfarin Therapy with Conventional-Intensity Warfarin Therapy for Long-Term Prevention of Recurrent Venous Thromboembolism

Abstract: Conventional-intensity warfarin therapy is more effective than low-intensity warfarin therapy for the long-term prevention of recurrent venous thromboembolism. The low-intensity warfarin regimen does not reduce the risk of clinically important bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
360
8
13

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 697 publications
(397 citation statements)
references
References 9 publications
16
360
8
13
Order By: Relevance
“…This is not the case with warfarin. Thus, the rate of recurrent VTE was higher with lower-intensity warfarin (target INR of 1.5-2) than with usual-intensity warfarin (target INR of 2-3) in The Extended Low-Intensity Anticoagulation for Thrombo-Embolism (ELATE) trial, 73 whereas rates of major bleeding were similar. Because the risk of bleeding is often the limiting factor in the decision to extend the duration of anticoagulation therapy, the results with low-dose apixaban may prompt more clinicians to prescribe extended VTE treatment.…”
Section: Doacs For Treatment Of Vtementioning
confidence: 99%
“…This is not the case with warfarin. Thus, the rate of recurrent VTE was higher with lower-intensity warfarin (target INR of 1.5-2) than with usual-intensity warfarin (target INR of 2-3) in The Extended Low-Intensity Anticoagulation for Thrombo-Embolism (ELATE) trial, 73 whereas rates of major bleeding were similar. Because the risk of bleeding is often the limiting factor in the decision to extend the duration of anticoagulation therapy, the results with low-dose apixaban may prompt more clinicians to prescribe extended VTE treatment.…”
Section: Doacs For Treatment Of Vtementioning
confidence: 99%
“…7 Previously, the Extended Low-Intensity Anticoagulation for ThromboEmbolism (ELATE) trial had suggested a better safety profile in patients on warfarin, with an annual incidence of any bleeding of only 3.7%. 8 This observation is likely attributable to a selection of low-risk participants in ELATE, which may also explain the similar bleeding risks observed in participants with target INR of 2.0 to 3.0 and of 1.5 to 1.9. Current alternatives to warfarin (with a target INR of 2.0-3.0) may have different, and perhaps better, efficacy/safety profiles and have been evaluated in several trials in the past 15 years (Tables 1 and 2): warfarin with a target INR of 1.5-2.0, 9 dabigatran 150 mg twice daily, 7 rivaroxaban 20 mg daily, 10 apixaban 2.5 or 5 mg twice daily, 11 and aspirin 100 mg. 12,13 New oral anticoagulants may perhaps cause less bleeding than warfarin with a target INR of 2.0 to 3.0, as demonstrated for dabigatran in the RE-MEDY trial (relative risk reduction, 29%) ( Table 2), whereas their protection against recurrent VTE remains substantial (relative risk reduction, 80% to 92% for rivaroxaban, dabigatran, or apixaban compared with placebo).…”
Section: Article See P 1891mentioning
confidence: 92%
“…De esta forma, se obtuvo el grupo estudio, conformado por 188 pacientes. Se registró en base a las fichas clínicas: Sexo, Edad, efectos adversos (hemorragias mayores y menores, definidas las primeras como aquellas que requirieron hospitalización y/o transfusiones) 11 , diagnóstico y justificación de inicio de ACO.…”
Section: Pacientes Y Métodounclassified
“…La literatura muestra a que el ACO más usado es warfarina, cuya ventaja aparentemente es una vida media más larga y mayor estabilidad en mantener los niveles terapéuticos, lo que aún es cuestionado 4,[9][10][11] .…”
Section: Introductionunclassified